Surface modification of oriented glass fibers for improving the mechanical properties and flame retardancy of polyamide 12 composites printed by powder bed fusion - Hou, Yanbei (2023)
The orientation of glass fibers (GF) introduced by powder bed fusion (PBF) imparts enhanced mechanical properties to polyamide 12 (PA12). However, there is still much room for reinforcement of PBF-printed GF/PA12 composites. In addition, no studies have addressed the flame retardancy of PBF-printed GF/PA12 composites impaired by the candlewick-like effect of GF. This work presents a feasible and practical approach for addressing these two issues, by surface modification of GF with layered double hydroxide (LDH) to synthesize LDH@GF hybrids. Compared with the ultimate tensile strength, Young's modulus, flexural strength, and flexural modulus of the GF/PA12 composites, those of the LDH@GF/PA12 composites increased by 21.3%, 54.3%, 31.8%, and 36.7%, respectively. Meanwhile, LDH weakened the candlewick-like effect of GF and thus improved the flame retardancy of the PA12 composites. Compared with the peak heat release rate and total heat release of the GF/PA12 composites, those of LDH@GF/PA12 composites were reduced by 17.7% and 12.7%, respectively. The mechanisms for mechanical reinforcement and flame retardancy of LDH@GF hybrids were investigated and proposed. This work paves the way for PBF to prepare flame-retardant high-strength PA12 composites and provides a new solution to boost the performance of additively manufactured products.